School entry level tele-hearing screening in a town in South India – Lessons learnt. (January 2017) - Monica, Saleth D; Ramkumar, Vidya; Krumm, Mark; Raman, Nitya; Nagarajan, Roopa; Venkatesh, Lakshmi
Abstract: Introduction: School screening is warranted in developing countries that do not have newborn hearing screening as schools provide access to a large number of young children between 3 and 5 years of age. Due to scarcity of technical manpower and equipment, hearing screening programs are not often conducted in developing countries. In these circumstances, telehealth services appear to be a reasonable solution. Consequently, the purpose of this study was to assess the feasibility of school hearing screening using telehealth technology operated by a practitioner located 400 kms away at a distant hospital. Method: Thirty one children received hearing screening procedures in their school. Each child was screened for both in-person and telehealth conditions to assess screening results. Remote computing software was employed for the telehealth condition in order for the practitioner to remotely operate an audiometer, DPOAE system and a video otoscope interfaced to a personal computer at the school site.Teamviewer version 10 was used to provide encrypted videoconferencing and synchronous hearing screening services between the hospital and school sites. All screening was conducted using a mobile phone hotspot or dongle device based internet connection to insure reliable connectivity. Results: The outcome revealed no significant difference between PTA and DPOAE performed in-person and tele-hearing screening methods. Concurrence of greater than 87% was achieved between in-person and tele-video-otoscopy. Strengths and challenges were documented for tele-hearing screening in three different dimensions: technical issues, child related and school related. Understanding these challenges may provide more effective tele-audiology services. Discussion: The results of the study indicate synchronous hearing screening services can be provided in a school setting using mobile hotspot or dongle connectivity in locations where Internet bandwidth is otherwise restricted.